Efficacy, Safety, and Sample Quality of Ultrasound‐Guided Synovial Needle Biopsy in Clinical Practice and Research: A Prospective Observational Study. Issue 10 (29th September 2020) - Romão, Vasco C.; Polido‐Pereira, Joaquim; Barros, Rita; Luís, Rita; Vidal, Bruno; Vieira‐Sousa, Elsa; Vitorino, Emília; Humby, Frances; Kelly, Stephen; Pitzalis, Costantino; Saraiva, Fernando; Fonseca, João Eurico
Abstract : Objective: To study the efficacy, tolerability, safety, and sampling variation of ultrasound (US)–guided synovial biopsies performed in clinical practice and research. Methods: We included all patients who had a US‐guided synovial needle biopsy from November 2013 to January 2018. Patients were evaluated for procedure safety and tolerability. Usefulness of synovial biopsy was considered based on contribution for achieving the proposed aims. We analyzed samples for presence and quality of synovial tissue, synovitis score/grade, and pathotype. Variation across patients, samples, section levels, and sampling order was assessed. Results: A total of 64 US‐guided synovial biopsies were performed (n = 52 in clinical practice, n = 12 in research). Patient tolerability (70% no/mild discomfort) was remarkably high. There was no significant aggravation of symptoms or US synovitis in the biopsied joint. Procedures were overall safe, with few minor, 2 moderate, and no major adverse events. Usefulness of US‐guided synovial biopsies was high, both in clinical practice (37% direct diagnostic impact, 100% positive/95% negative predictive values for infection) and in research (92% success). Synovial tissue was retrieved in 88% of biopsies, with a median of 75% gradable samples. There was significant variation in sample quality and synovitis features across patients and samples, but not between different section levels. Samples collected later in the procedure had a lower frequency of synovial tissue and were poorly concordant in pathotype with those collected earlier. Conclusion: US‐guided synovial needle biopsy is an effective, safe, and well‐tolerated means to collect good quality synovial tissue for clinical and research purposes. Samples collected for different aims should be retrieved in parallel, rather than sequentially.